Potencial de radônio no ar de ambientes interiores residenciais: aspectos geológicos e construtivos da Região Metropolitana de Belo Horizonte - Evelise Gomes Lara (2017)
International regulatory bodies have been presented orientation that countries shall to identify susceptible areas to radon and investigate the building features that may contribute to increased exposure of the inhabitants. The goal of this study was to evaluate the radon potential indoor air of Metropolitan Region of Belo Horizonte (RMBH) according to its geological characteristics and construction standards patterns in Brazil. Thus, were evaluated the physicochemical features of predominant soils types of the region; the features of the main floors used in residential buildings; the exhalation rates of radon from the soil; the concentration of radon indoor the single dwellings and, finally, the annual dose estimates in the inhabitants. The geological features were considered by using the information from the Brazilian Agricultural Research Company (Embrapa), the local measurements of the soil radon concentrations were obtained through the AlphaGUARD® monitor and the determination of the permeability by using the RADON-JOK® permeameter. In addition, the analytical techniques of gamma spectrometry (HPGe), mass spectrometry (ICP-MS) and X-ray diffraction made it possible to consider the levels of 226Ra, U elemental and mineralogical characterization of the soil samples, respectively. Estimates of exhalation rates and radon transport model were based on methodologies established in the scientific international literature. Regarding the building aspects, the most used floors in the residential standards were selected in agreement with the Brazilian standards. The combinations of soil radon concentrations and permeabilities showed coherence with the radon concentrations estimated in the Brazilian buildings. Approximately 45% of the soils measured could be classified as a medium or high-risk level for radon potential, especially in areas where latosols predominate, where more than half of the soils presented a high risk. No significant correlations were detected between the concentrations of radon and uranium in the soils of the RMBH. The mineralogical characterization of soils presented a mineralogy typical of tropical climate areas, with the predominance of primary minerals quartz and muscovite and secondary minerals such as kaolinite, gibbsite, and calcite. The estimation of the exhalation rate of radon from the soil to the atmosphere in areas that Red Latosols predominated was about four times higher when compared to the areas of Litolic Neosols. Regarding the building aspects, it was estimated that approximately 20% of the radon that exudes at the surface of the soil can flow through the concrete slab of a single dwelling. For floors, about 2% of the radon from the soil surface flows through the porcelain floor, 15% crosses the ceramic floor considered for the normal residence pattern and about 17% can flow through the ceramic floor used in the low building pattern. The combination of geological and building aspects allowed to estimating the radon in the air of the residences using a more integrated approach, associating to the building projects the environmental characteristics of the environment in which these projects are or will be constructed